The Role of Financial Accounting and Auditing in Protection of Intellectual Property Rights - El-Hussein, Omer Mahgoub (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this study was to explore the role of accounting and auditing, and to what extent, they contribute to the protection of intellectual property. These rights are related to legal concerns in the revenue realization principle. This common goal is for the protection of intellectual property rights, though different tools and procedures and used. The study furthermore. Was aimed to shed light on the views of people working in accounting and legal domains, about the financial accounting role in the protection of intellectual property.The researcher followed the descriptive-analytical method, using the questionnaire as a tool for the collection of data from specialists, to verify the hypotheses. of the study.Analysis of data revealed several results, the importance of which showed that financial accounting contributes to the protection of intellectual property rights. In addition to that, it showed that there is a difference in the ways used by accountants and legal framework in the definition of intellectual property rights, it was also clear that the accounting and auditing standards are different from the legal principles. But, despite that, it is considered as a legal framework to realize a fair and real value for the assets of intellectual property.The results of the study also showed that the purpose of available Laws of intellectual property is to give innovators the chance to make use of the incomes resulting from their efforts but in the case of accountancy the intellectual property is considered as an intangible asset that generates revenue. Furthermore, The income from intellectual an end after a certain period from the legal point of view. But in the case of accountancy, the intellectual property is an asset whose income continues and does not end except by amortization, or by transfer of property to other parts.The protection of intellectual property is an important issue; for this reason, The rules and standards governing it must be integrated into accountancy, audit, and roles of law to provide enough protection for intellectual property in addition to unification of the ways dealing with it legally and in the accounting procedures.
Keywords: Intellectual Property; Intellectual Property Rights; Intellectual Capital; Intellectual Property Audits